Personality Traits Orientation of University Kebangsaan Malaysia (UKM) and UKM - University Duisburg-Essen (UDE) Engineering Students - Mastor, KA; Sulehan, J; Mustafa, J; Pawanteh, L; Basri, H; Abdullah, S; Mokthtar, A; Abd Ghani, Z; Axel, H (Elsevier Science Bv, 2024)
The study aims to investigate the personality trait orientation of engineering students at UKM, alumni and the current students participating in the UKM-UDE double degree program. It is hypothesized that personality trait profile might be different between these respondents due to different academic, social and cultural background the students experienced. A total number of 54 respondents (19 alumni, 12 current students and 23 potential UKM engineering students) participated in the study. The 44 Big Five Inventory (John et al, 1991) was used to assess the personality profile. Data analyzed indicated some significant differences as expected. The current UKM-UDE engineering students were high on Neuroticism than those of UKM engineering students and UKM-UDE alumni. The alumni and current UKM-UDE students scored lower on Extraversion compared to the current local UKM engineering students. Current and the alumni of the UKM-UDE students scored higher on Openness than the current UKM engineering students. Overall findings suggest that environmental and socio-cultural factor play important role in the development of personal characteristics. Implications of the study on the benefits of the student mobility and exchange program were also discussed. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of Kongres Pengajaran & Pembelajaran UKM, 2010